Effect of raloxifene therapy on venous thromboembolism in postmenopausal women: A meta-analysis - Adomaityte, Jurga; Farooq, Maria; Qayyum, Rehan (Thrombosis and Haemostasis, 2008)
Raloxifene, a selective estrogen receptor modulator, is indicated for the prevention of osteoporosis in postmenopausal women. However, its effect on the risk of deep venous thrombosis (DVT) and pulmonary embolism (PE) is unclear. Therefore, we conducted a meta-analysis to evaluate the effect of raloxifene on these outcomes. To identify randomized controlled trials of raloxifene, a systematic search of PubMed, EMBASE, and Cochrane Collaboration databases was performed from the date of inception of these databases to October 2007. Search was limited to trials that were published in peer-reviewed English-language medical journals. Articles were included in the meta-analysis if they had reported on DVT, PE, or thromboembolic events. Nine trials, including 24,523 postmenopausal women, (median age 59.4 years, range 55 to 67 years; median follow-up 24 months, range 3 to 67 months) met inclusion criteria. Therapy with raloxifene was associated with a 62% increase in odds of either DVT or PE (odds ratio = 1.62; 95% confidence interval = 1.25 to 2.09; p-value < 0.001). Similarly, raloxifene therapy was associated with 54% increase in odds of DVT (odds ratio = 1.54; 95% confidence interval = 1.13 to 2.11; p-value = 0.006) and 91% increase in odds of PE alone (odds ratio = 1.91;95% confidence interval = 1.05 to 3.47; p-value = 0.03). Raloxifene increases the risk of DVT and PE in postmenopausal women.
Keywords: Raloxifene; deep venous thrombosis; pulmonary embolism; venous thromboembolism